Enlargement of the genial tubercles: a case report - Oliveira, Luciana Soares de Andrade Freitas; Vidal, Manuela Torres Andion; Valverde, Ludmila Faro; Crusoé-Rebello, Iêda Margarida (Journal of Oral Diagnosis, 2016)
The genial tubercles are small bony protuberances located in the cortical lingual of the mandible, in the midline. The enlargement of the genial tubercles is more common in edentulous mandibles exhibiting bone resorption, is generally asymptomatic and diagnosed by routine imaging methods. This study describes a case of enlargement of the genial tubercles detected by cone-beam computed tomography prior to the placement of dental implants. Cone-beam computed tomography showed an unusual increase in size and volume on the inner surface of the mandible, in the midline, which had a pedunculated aspect and was similar in density to cortical bone, suggested enlargement of the genial tubercles. In conclusion, this bone prominence should be observed during the planning of rehabilitation treatment since its presence can influence the adaptation of dentures. Additionally, patients should be monitored regarding painful symptoms and the presence of fractures, with surgical removal being required in some cases.